Magnetic resonance imaging versus transvaginal ultrasound for complete survey of the pelvic compartments among patients with deep infiltrating endometriosis. Issue 3 (15th July 2019) - Hernández Gutiérrez, Alicia; Spagnolo, Emanuela; Hidalgo, Paula; López, Ana; Zapardiel, Ignacio; Rodriguez, Roberto
Abstract: Objective: To compare the performance of magnetic resonance imaging (MRI) and transvaginal ultrasound (TVU) in detecting deep infiltrating endometriosis (DIE), using Enzian classification. Secondarily, to evaluate the influence of nodule size on the accuracy of MRI and TVU. Methods: A retrospective study was carried out at "La Paz" University Hospital, Madrid, Spain, between April 2012 and December 2014. Inclusion criteria were suspicion of DIE at gynecologic examination, indication to undergo TVU, MRI and surgery. Exclusion criteria were previous hysterectomy, bowel resection, or urinary tract surgery. The diagnosis of DIE using MRI or TVU was considered positive when it correlated with histology. Sensitivity, specificity, accuracy, and mean size of the nodule were calculated. Results: In the present study involving 48 women, TVU demonstrated greater accuracy than MRI for recto‐vaginal (77% vs 69%) and vaginal (94% vs 89%) endometriosis. MRI showed greater accuracy (96%) than TVU (92%) for bladder endometriosis. The size of the nodule did not have a significantly different effect on the accuracy of TVU compared with MRI. Conclusion: In the present study, TVU provided a more accurate localization of vaginal and recto‐vaginal endometriosis as compared with MRI; however, MRI should be recommended if a suspicion of bladder endometriosis exists. The nodule size did not seem to influence the accuracy of the two techniques. Abstract : Transvaginal ultrasound showed a higher accuracy compared to magnetic resonance in diagnosing recto‐vaginal endometriosis. Magnetic resonance should be recommended if suspicion of bladder endometriosis exists.